Existence Results for a Class of p-Laplacian Fractional Differential Equations with Integral Boundary Conditions. (1st May 2020) - Pak, SunAe; Jong, KumSong; O, KyuNam; Choi, HuiChol
Abstract : In this paper, we investigate the existence and uniqueness of solutions for a class of integral boundary value problems of nonlinear fractional differential equations with p - Laplacian operator. We obtain some existence and uniqueness results concerned with our problem by using Schaefer's fixed-point theorem and Banach contraction mapping principle. Finally, we present some examples to illustrate our main results.